Synthesis of d‐mannitol‐based crown ethers and their application as catalyst in asymmetric phase transfer reactions. Issue 4 (28th December 2017) - Nemcsok, Tamás; Rapi, Zsolt; Keglevich, György; Grün, Alajos; Bakó, Péter
Abstract: A few newd ‐mannitol‐based monoaza‐15‐crown‐5 type chiral lariat ethers and 18‐crown‐6 type macrocycles were synthesized. These crown compounds were used as phase transfer catalysts in asymmetric Michael addititons and in a Darzens condensation under mild conditions to afford the corresponding products in a few cases in good to excellent enantioselectivities. In the Michael addition of diethyl acetoxymalonate to trans ‐chalcone, in the addition of diethyl acetamidomalonate to ß ‐nitrostyrene, in the reaction of diethyl bromomalonate with benzylidene malononitriles, in the cyclopropanation reaction of diethyl bromomalonate and 2‐benzylidene‐1, 3‐indandione, and in the Darzens condensation of α ‐chloroacetophenone with benzaldehyde, maximum enantioselectivities of 39%, 65%, 99%, 56%, and 62%, respectively, were obtained in the presence of thed ‐mannitol‐based macrocycles as the catalysts. Abstract :